The Role of Village-Owned Enterprises in Improving Community Welfare in Gunungtawang Village, Selomerto District - Romandhon Romandhon; Bambang Agus Pramuka; Puji Lestari (Proceedings Series on Social Sciences & Humanities, 2024)
Background : The village-owned enterprise ( BUMDes ) "Sepoor Bridge" has been able to provide village revenue from the results of the clean water supply business unit, but has not been able to have a major influence on improving the general welfare of the community. Methods : This study used a descriptive qualitative approach, namely through observation, interviews, and documentation. Results : The Village-Owned Enterprise "Sepoor Bridge" still relies on one business unit and its revenue is still used to add equipment, channel installation tools, and payment for water sources. Conclusion : The Village-Owned Enterprise " Sepoor Bridge " can help the community save on clean water costs and make it easier to get it.